Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 5 - Polynomials and Factoring - 5.2 Factoring Trinomials of the Type x2+bx+c - 5.2 Exercise Set: 35

Answer

$x^3(x-2)(x+1)$

Work Step by Step

Factoring the $GCF= x^3 $, the given expression, $ x^5-x^4-2x^3 ,$ is equivalent to \begin{array}{l} x^3(x^2-x-2) .\end{array} The 2 numbers whose product is $ac= 1(-2)=-2 $ and whose sum is $b= -1 $ are $\left\{ -2,1 \right\}.$ Using these two numbers to decompose the middle term of the above trinomial, then \begin{array}{l} x^3(x^2-2x+1x-2) \\\\= x^3[(x^2-2x)+(1x-2)] \\\\= x^3[x(x-2)+(x+2)] \\\\= x^3[(x-2)(x+1)] \\\\= x^3(x-2)(x+1) .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.